Awareness Regarding Premenstrual Syndrome among Adolescent Girls in a School of Rupandehi - Bhanadari, Sharmila; Lamichhane, Kavita; Kachapati, Anuja; Bajracharya, Srishti; Rawal, Shristee; Bhattarai, Kalpana (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Premenstrual syndrome is common condition that affects adolescent girl’s emotions, physical health and behavior during certain days of menstrual cycle, generally just before menstruation. The present study aims to identify awareness regarding premenstrual syndrome among adolescent girls of a school. MATERIAL AND METHODS A descriptive cross sectional study was conducted to assess awareness regarding premenstrual syndrome among 236 adolescent girls in a school of Rupandehi by using non-probability purposive sampling technique. Self-administered questionnaire was used to collect the data and collected data were analyzed by using descriptive and inferential statistics. RESULTS The ﬁndings of the study revealed that 53.4% of the respondents had low level of awareness. There was statistically signiﬁcant association between mother’s occupation and awareness level (p=0.024). CONCLUSION Based on the study ﬁndings, it is concluded that more than half of the adolescent girls had low level of awareness so; it is recommended for promoting and upgrading girl’s awareness for effective coping and management in school.